Emotional Distress in a Patients Following Polytrauma - Anghele M; Marina V; Moscu CA; Dragomir L; Anghele AD; Lescai AM (Journal of Multidisciplinary Healthcare, 2023)
Mihaela Anghele,1 Virginia Marina,2 Cosmina Alina Moscu,3 Liliana Dragomir,1 Aurelian-Dumitrache Anghele,2 Alina-Maria Lescai1 1Clinical-Medical Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galati, Galati, 800201, Romania; 2Medical Department of Occupational Health, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galati, Galati, 800201, Romania; 3Emergency Hospital, Faculty of Medicine and Pharmacy, “Dunarea de Jos” University of Galati, Galati, 800201, RomaniaCorrespondence: Virginia Marina, Tel +40-770-89-82-74, Email virginia.marina@ugal.roIntroduction: Emotional affectivity can be described under two general dimensions: positive affectivity and negative affectivity. It is often assessed by means of questionnaires completed retrospectively by the subjects. The most common scales used are PANAS, DES, and PANA-X. All these scales are based on the concept of two dimensions, negative and positive affective emotions, respectively. Both dimensions mentioned, positive and negative affectivity, can be associated with a bipolar dimensional entity called pleasant-unpleasant. Specifically, a high level of positive emotions and a low level of negative emotions are associated with pleasant/positive feelings (happiness, well-being, satisfaction, cheerfulness, etc.), while a low level of positive emotions and a high level of negative emotions are associated with negative feelings (sadness, anger, nervousness, depression, anxiety, etc.).Materials and Methods: This study is an observational and cross-sectional study. The elements that led to the production of the final database were collected by means of a questionnaire, which included 43 items, 39 of which were specific questions found in the affective distress profile. The questionnaire was administered to 145 patients who had suffered polytrauma and were admitted to the Emergency Hospital of Galati in October 2022. The final centralizing tables included the characteristics of 145 patients, aged between 14 and 64 years.Results: The aim of this study is to identify the level of emotional distress in patients who have suffered polytrauma, so the following scores were evaluated, obtained after the application of PDA: STD, ENF, END. The total distress score was obtained by summing all the negative items found in the PDA questionnaire.Conclusion: Men show a high level of emotional distress compared to women. Polytrauma has a negative effect on patients’ emotional status, with a worrying prevalence of negative functional and dysfunctional emotions. The level of distress in polytrauma patients is high.Keywords: emotional distress, polytrauma, affective dysfunctions, emotions